Broad Reach and Targeted Recruitment Using Facebook for an Online Survey of Young Adult Substance Use - Ramo, Danielle E (Gunther Eysenbach, 2012)
BACKGROUND: Studies of tobacco use and other health behaviors have reported great challenges in recruiting young adults. Social media is widely used by young adults in the United States and represents a potentially fast, affordable method of recruiting study participants for survey research. OBJECTIVE: The present study examined Facebook as a mechanism to reach and survey young adults about tobacco and other substance use. METHODS: Participants were cigarette users, age 18-25 years old, living throughout the United States and recruited through Facebook to complete a survey about tobacco and other substance use. Paid advertising using Facebook’s Ad program over 13 months from 2010 Feb 28 to 2011 Apr 4 targeted by age (18-25), location (United States or California), language (English), and tobacco- and/or marijuana-related keywords. Facebook approved all ads. RESULTS: The campaign used 20 ads, which generated 28,683,151 impressions, yielding 14,808 clicks (0.7% of targeted Facebook members), at an overall cost of $6,628.24. The average cost per click on an ad was $0.45. The success of individual ads varied widely. There was a rise in both clicks and impressions as the campaign grew. However, the peak for clicks was 3 months before the peak for ad impressions. Of the 69,937,080 accounts for those age 18-25 in the United States, Facebook estimated that 2.8% (n = 1,980,240) were reached through tobacco and marijuana keywords. Our campaign yielded 5237 signed consents (35.4% of clicks), of which 3093 (59%) met criteria, and 1548 (50% of those who met criteria) completed the survey. The final cost per valid completed survey was $4.28. The majority of completed surveys came from whites (69%) and males (72%). The sample averaged 8.9 cigarettes per day (SD 7.5), 3.8 years of smoking (SD 2.9), with a median of 1 lifetime quit attempts; 48% did not intend to quit smoking in the next 6 months. CONCLUSIONS: Despite wide variety in the success of individual ads and potential concerns about sample representativeness, Facebook was a useful, cost-effective recruitment source for young-adult smokers to complete a survey about the use of tobacco and other substances. The current findings support Facebook as a viable recruitment option for assessment of health behavior in young adults.